MENGKAJI KEDUDUKAN ZAKAT TERHADAP TABUNGAN BANK DALAM TINJAUAN HUKUM ISLAM - Sadat, Anwar; Karimuddin, Karimuddin; Sagita , Fatri (Al-Daulah : Journal of Criminal Law and State Administration Law, 2024)
Research Objective: The study aims to provide a comprehensive overview of Islamic legal perspectives on zakat for savings and to clarify the requirements and conditions under which zakat should be paid on savings and interest earned from bank deposits. Research Methodology: The study employs the Uṣūl al-Fiqh methodology, utilizing comparative techniques through literature reviews and analysis of current societal trends, examining both classical Islamic jurisprudence and contemporary interpretations. Results: The research findings reveal that zakat must be paid on bank savings if they meet established criteria in zakat regulations. Regarding interest earned on savings, zakat should be paid according to the views of scholars who permit accepting interest. Findings and Implications: The study provides comprehensive analysis offering valuable insights into zakat obligations on savings and interest, serving as guidance for Muslims seeking to adhere to Islamic law in their financial practices. Conclusion: The research concludes that specific Islamic legal requirements exist for paying zakat on both savings and interest earnings, with different scholarly perspectives influencing their application. Modern banking practices can be reconciled with traditional zakat obligations through careful jurisprudential analysis. Contribution: The study bridges classical Islamic jurisprudence with contemporary interpretations regarding zakat obligations on modern banking practices. This research fills a critical gap by offering practical guidance for contemporary Muslim financial conduct while maintaining scholarly rigor in Islamic legal analysis. Limitations: The research primarily relies on existing literature without empirical analysis of actual zakat practices among contemporary Muslims. focus may limit practical applicability across diverse socio-economic contexts. Suggestions: Future research should incorporate empirical studies examining zakat payment behaviors among Muslim savers and investors. Comparative cross-cultural analysis would enhance understanding of how different Islamic societies interpret zakat obligations on modern financial instruments.